Modelling of rural electrical appliances saturation in developing countries to project their electricity demand: A case study of sub-Saharan Africa - Dominguez, Cristina; Orehounig, Kristina; Carmeliet, Jan (International Journal of Sustainable Energy Planning and Management, 2019)
Rural electrification projects are mostly listed as a priority in developing countries due to the numerous benefits it brings to improve people’s quality of life. The starting point for these projects is the accurate estimation of the households’ energy demand, but the large amount of resources that requires the on-site data collection makes this process unattractive to investors. This paper brings a potential solution to that matter, presenting a methodology for modelling the appliances saturation of rural households in developing countries to project their electricity demand. Based on a statistical approach, and including training data from more than 1,100 household samples from Nigeria and Ethiopia, the correlation between household survey data of saturation rates of the most common electricity-consuming appliances in developing countries and different socio-economic, demographic and geographic variables are investigated. Its accuracy is tested using other sets of validation data at a household, state, and national level. Finally, the results are projected using a Geographic Information Systems approach for identifying possible sites to be electrified. The high potential of using this approach for projecting the appliances saturation rates for rural areas was proven by obtaining a good overall accuracy in the results. As expected, the errors obtained at a household level were bigger than at a state or national level, these deviations are attributed to the presence of outliers due to the human behaviour incidence at household scale; which also affects the correlation patterns between the appliances ownership and evident socioeconomic factors.